Biliary calprotectin, lactoferrin and dimeric pyruvate kinase after liver transplantation are associated with biliary damage and graft survival in a case-control study - Rauber, Conrad; Awad, Miriam; Koschny, Ronald; Sauer, Peter; Mehrabi, Arianeb; Gath, Philip; Weiss, Karl Heinz; Gotthardt, Daniel; Rupp, Christian (Clinics and research in hepatology and gastroenterology, 2020)
Background - After liver transplantation (LT), biliary complications are associated with reduced graft survival. We tested inflammation markers for their association with biliary damage and graft loss in bile. - Material and methods - The study design was a retrospective case-control study. Calprotectin, lactoferrin and pyruvate kinase were measured in endoscopically retrieved bile with ELISA. - Results - Calprotectin and lactoferrin were significantly higher in bile of ischemic-type biliary lesions and donor duct non-anastomotic strictures than in control, bile leakage, Cytomegalovirus infection, anastomotic stricture or acute cellular rejection patients (p<0.001) independent of serum liver values at endoscopy. Calprotectin (p=0.02) was independently associated with retransplantation free survival in multivariate analysis, as was γGT (p=0.03) but not ERC radiographic classification of the bile duct or cold ischemia time. - Conclusion - Calprotectin and lactoferrin are bile markers for biliary damage and are associated with re-transplantation free survival. They can differentiate progressive biliary damage from non-biliary liver value alterations after LT.
Online 11 June 2019
Gesehen am 11.05.2020